The impact of psychological status and quality of life of employees on presenteeism in the health-work relationship after earthquakes in Türkiye - Koca, Mehmet; İnceoğlu, Feyza; Deniz, Serdar (The European Research Journal, 2025)
Objectives: This study aims to investigate the workers' general health, psychological status, and quality of life perception on presenteeism after the major earthquakes on Türkiye in the relationship between health and labor. Methods: This study was conducted at Baykan Denim Company, which manufactures in Malatya, with the participation of 327 employees. Data were collected using the socio-demographic questionnaire form, the Attitude Scale for Determining the Psychological Status of Individuals Exposed to Earthquakes, the General Health Questionnaire-12, the Quality of Life Scale and the Presenteeism Scale. Results: The findings showed that the Attitude Scale for Determining the Psychological Status of Individuals Exposed to Earthquakes scores had a positive statistically significant effect on Presenteeism (β1=0.443; P=0.001) and General Health (β1=0.495; P=0.001) scores and a negative statistically significant effect on the Quality of Life (β1=-0.145; P=0.001) scores. Presenteeism scores had a positive and statistically significant effect on general health (β1=0.183; P=0.001) and Quality of Life (β1=0.131; P=0.009) scores. Presenteeism scores increased as general health and the Quality of Life scores increased. Conclusions: This study concluded that individuals were mentally impacted by the earthquake. This impact was seen in individuals’ overall health perception and quality of life, leading to elevated presenteeism rates.